A sensorimotor enhanced neuromusculoskeletal model for simulating postural control of upright standing - Shanbhag, Julian; Fleischmann, Sophie; Wechsler, Iris; Gassner, Heiko; Winkler, Jürgen; Eskofier, Bjoern M.; Koelewijn, Anne D.; Wartzack, Sandro; Miehling, Jörg (Frontiers in Neuroscience, 2024)
The human's upright standing is a complex control process that is not yet fully understood. Postural control models can provide insights into the body's internal control processes of balance behavior. Using physiologically plausible models can also help explaining pathophysiological motion behavior. In this paper, we introduce a neuromusculoskeletal postural control model using sensor feedback consisting of somatosensory, vestibular and visual information. The sagittal plane model was restricted to effectively six degrees of freedom and consisted of nine muscles per leg. Physiologically plausible neural delays were considered for balance control. We applied forward dynamic simulations and a single shooting approach to generate healthy reactive balance behavior during quiet and perturbed upright standing. Control parameters were optimized to minimize muscle effort. We showed that our model is capable of fulfilling the applied tasks successfully. We observed joint angles and ranges of motion in physiologically plausible ranges and comparable to experimental data. This model represents the starting point for subsequent simulations of pathophysiological postural control behavior.